Tech Recruiting Foundations: 2 Understanding Hardware and Operating Systems. - Shaikh, Ayub; Consulting, Holistica (linkedin.com, 2021)
Learn enough about hardware and operating systems to be able to recruit and hire effectively for related roles in IT.